Between the Iron Cage and the Learning Organization: A Comparative Study of Modern and Critical Organization Theory - Akdila Bulanov; Fanisa Mutiara; Wafiq Azizah; Siti Aisyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research aims to examine modern organizational theory and critical organizational theory as two emerging approaches within organizational science. Modern organizational theory views organizations as open systems that must adapt to the external environment through structural flexibility, transformational leadership, learning organizations, and the use of technology and knowledge management. Meanwhile, critical organizational theory presents itself as an approach that questions the relations of power, domination, ideology, and alienation within organizational life.